Environmental psychology an introduction - Steg, Linda; Berg, Agnes E. van den.; de Groot, Judith I. M.; ebrary, Inc. (Chichester [England] ; Malden, Mass. : Wiley-Blackwell, 2013)
"Explores the environment's effects on human wellbeing and behaviour, factors influencing environmental behaviour and ways of encouraging pro-environmental action"--
pt. 1. Environmental influences on human behaviour and well-being -- pt. 2. Factors influencing environmental behaviour -- pt. 3. Encouraging pro-environmental behaviour.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Environmental psychology; Electronic books